Pengaruh Aset Produktif dan Non Produktif Terhadap Profitabilitas Bank Central Asia Syariah Periode Tahun 2017 - 2021 - Lailatul Mukaromah; Diah Krisnaningsih (Jurnal Ilmiah Ekonomi Islam, 2023)
One of the important components in Bank Central Asia Syariah is Earning and Non-Earning Assets. In these two components have an influential impact on profitability. The function of this component is channeling funds to the community. This study aims to determine how much influence productive and non-productive assets have on profitability at Bank Central Asia Syariah for the period 2017 – 2021, the research method used is quantitative methods and secondary data obtained from Bank Central Asia Syariah monthly reports. The results of this study state that productive assets and non-productive assets have a simultaneous but not significant effect on profitability. Because the profits from productive assets can still cover the losses incurred by non-productive assets